2017
DOI: 10.1021/acscentsci.7b00014
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic N2-to-NH3 Conversion by Fe at Lower Driving Force: A Proposed Role for Metallocene-Mediated PCET

Abstract: We have recently reported on several Fe catalysts for N2-to-NH3 conversion that operate at low temperature (−78 °C) and atmospheric pressure while relying on a very strong reductant (KC8) and acid ([H(OEt2)2][BArF4]). Here we show that our original catalyst system, P3BFe, achieves both significantly improved efficiency for NH3 formation (up to 72% for e– delivery) and a comparatively high turnover number for a synthetic molecular Fe catalyst (84 equiv of NH3 per Fe site), when employing a significantly weaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
278
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 206 publications
(297 citation statements)
references
References 46 publications
13
278
4
Order By: Relevance
“…8 Of particular interest has been to distinguish between an early Chatt-type cleavage pathway (a distal mechanism via an Fe≡N intermediate) and a late-stage cleavage pathway (an alternating mechanism via an Fe—N 2 H 4 intermediate). 9 While we have considered the possibility that both scenarios might be viable, 10 a key feature of the tri(phosphine)borane Fe system is its structurally and electronically flexible Fe—B interaction, which allows access to both reduced trigonal bipyramidal Fe(N 2 ) species as well as, in principle, pseudotetrahedral terminal Fe≡N.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…8 Of particular interest has been to distinguish between an early Chatt-type cleavage pathway (a distal mechanism via an Fe≡N intermediate) and a late-stage cleavage pathway (an alternating mechanism via an Fe—N 2 H 4 intermediate). 9 While we have considered the possibility that both scenarios might be viable, 10 a key feature of the tri(phosphine)borane Fe system is its structurally and electronically flexible Fe—B interaction, which allows access to both reduced trigonal bipyramidal Fe(N 2 ) species as well as, in principle, pseudotetrahedral terminal Fe≡N.…”
mentioning
confidence: 99%
“…8 In a separate synthetic study, it was shown that [(P 3 B )Fe(N 2 )] − reacts rapidly with excess HBAr F 4 at very low temperatures to form the cationic hydrazido(2−) complex [(P 3 B )Fe(NNH 2 )] + (Scheme 1C; potentials shown are measured in THF vs the ferrocenium/ferrocene couple [Fc + /Fc]). 12 To probe further steps in the catalytic N 2 fixation mechanism, we therefore sought access to the one-electron reduced hydrazido complex (P 3 B )Fe(NNH 2 ) to evaluate the viability of N—N bond cleavage via subsequent protonation.…”
mentioning
confidence: 99%
See 3 more Smart Citations